2020
DOI: 10.1136/bmjopen-2019-034152
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of acupuncture and moxibustion for defecation dysfunction after sphincter-preserving surgery for rectal cancer: protocol for systematic review and meta-analysis

Abstract: IntroductionDefecation dysfunction (DD) is one of the most common complications following sphincter-preserving surgery for rectal cancer. And there is no effective treatment of DD after sphincter-preserving surgery for rectal cancer. Although some studies suggested that acupuncture and moxibustion (AM) is effective and safe for DD after sphincter-preserving surgery for rectal cancer, lacking strong evidence, for instance, the relevant systematic review, meta-analysis and randomised controlled trial (RCT) of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Current western medical interventions such as gastrointestinal decompression and oral administered prokinetic medications have shown unsatisfactory results in patients, leading to the search for alternative treatment options by clinical practitioners, to facilitate early recovery of gastrointestinal functions [ 7 ]. Acupuncture is a safe and effective treatment method that could promote gastrointestinal functions while having minimal side effects [ 13 , 15 ]. Although current studies have shown the duration of PGID could be reduced through acupuncture, research on acupuncture and its role and therapeutic effect in the prevention of PGID in colorectal cancer patients has not been studied [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current western medical interventions such as gastrointestinal decompression and oral administered prokinetic medications have shown unsatisfactory results in patients, leading to the search for alternative treatment options by clinical practitioners, to facilitate early recovery of gastrointestinal functions [ 7 ]. Acupuncture is a safe and effective treatment method that could promote gastrointestinal functions while having minimal side effects [ 13 , 15 ]. Although current studies have shown the duration of PGID could be reduced through acupuncture, research on acupuncture and its role and therapeutic effect in the prevention of PGID in colorectal cancer patients has not been studied [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shows that [ 13 , 14 ] acupuncture exhibits higher effectiveness over western medications, displaying various advantages such as expediting the recovery of gastrointestinal function, reducing postoperative complications, boosting immunity, and improving quality of life, when applied as a complementary treatment for colorectal cancer. Additionally, acupuncture possesses qualities of a safe and economical treatment and holds an irreplaceable role in rehabilitation medicine [ 15 ]. However, existing studies have their limitations, including small study samples, poorly designed experiments, low credibility of experimental results, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted the systematic review in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement, and the protocol of this systematic review and meta-analysis has been registered on PROSPERO ( https://www.crd.york.ac.uk/PROSPERO , https://clinicaltrials.gov/ct2/show/CRD42019140097 ), registered on 5 Sep. 2019, and published on BMJ open [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The acupuncture operation in this single-arm study follows the theory of meridians and collaterals in TCM. In clinical practice, electroacupuncture was determined to be beneficial for LARS control, and the researches on acupuncture for defecation dysfunction after sphincterpreserving surgery for rectal cancer also showed potential effects [23].…”
Section: Acupuncture Interventionmentioning
confidence: 99%